Quality evaluation of Lonicerae Japonicae Flos and Lonicerae Flos based on simultaneous determination of multiple bioactive constituents combined with multivariate statistical analysis. Issue 2 (14th August 2019) - Cai, Zhichen; Wang, Chengcheng; Chen, Cuihua; Zou, Lisi; Chai, Chuan; Chen, Jiali; Tan, Mengxia; Liu, Xunhong
Abstract: Introduction: Lonicerae Japonicae Flos (LJF) and Lonicerae Flos (LF) belong to different genera of Caprifoliaceae. They have been historically utilised as herbal medicine to treat various diseases. However, the comprehensive assessment of them still remains a challenge. Objective: To develop a comprehensive method of ultra‐fast liquid chromatography‐tandem triple quadrupole mass spectrometry (UFLC‐QTRAP‐MS/MS) coupled with multivariate statistical analysis for the quality evaluation and reveal differential components of LJF and LF. Methodology: A validated UFLC‐QTRAP‐MS/MS method was established for simultaneous determination of 50 constituents, including 12 organic acids, 12 flavonoids, 6 iridoids, 3 saponins, 13 amino acids and 4 nucleosides. The obtained data were employed to multivariate statistical analysis. Principal component anlysis (PCA) and partial least squares determinant analysis (PLS‐DA) were performed to classify and reveal differential components of samples; grey relational analysis (GRA) was introduced to assess the samples according to the contents of 50 constituents by calculating the relative correlation degree of each sample. Results: Fifty constituents were simultaneously determined of LJF and LF. Based on obtained data, PCA and PLS‐DA were easy to distinguish samples and the classification of the samples was related to 11 chemical constituents. GRA implied the quality of LJF was better, and that the flower buds were superior to the flowers. Moreover, organic acids are the main components of samples. Conclusion: This study not only established a method of simultaneous determination of multiple bioactive constituents in LJF and LF, but provided comprehensive information on the quality control of them. The developed method is conducive to distinguish orthologues or paralogues of them, and supply the support for "heterologous effects". Abstract : A sensitive and comprehensive method employing UFLC‐QTRAP‐MS/MS coupled with multivariate statistical analyses was established to evaluate the quality of LJF and LF. A total number of 50 constituents, including 12 organic acids, 12 flavonoids, 6 iridoids, 3 saponins, 13 amino acids, and 4 nucleosides were simultaneously assayed in LJF and LF. Our study not only established a method of simultaneous determination multiple types of bioactive constituents of LJF and LF but provided comprehensive information on the quality control of them.